The lost symbol a novel - Brown, Dan 1964- (New York Doubleday, 2009)
Symbologist Robert Langdon returns in this new thriller follow-up to The Da Vinci Code.
UCWS-2848g donated by Patrick Valero.
Keywords: Cryptographers -- Fiction; Freemasonry -- Fiction; Suspense fiction; Adventure stories; Washington (D.C.) -- Fiction